2008
DOI: 10.1177/1059840523452345
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Middle School Students Into Nursing

Abstract: The purpose of this literature review is to illustrate the importance of initiating nursing recruitment during the middle school years. Data sources included citations from the years 1989 to 2006. The study focused on middle school students 9 to 13 years of age in Grades 6 to 8. One survey compared middle school students' perceptions of an ideal career and a career in nursing. Other studies discussed interventions such as nursing camps, recruitment videos, presentations, and handouts. After the intervention, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…Students often begin investigating career choices and discussing their future plans in middle school (Matutina, 2008). Hoke (2006) noted that 33% of those who ultimately choose nursing do so at an early age, and their choice is often based on stereotyping instead of awareness of the opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students often begin investigating career choices and discussing their future plans in middle school (Matutina, 2008). Hoke (2006) noted that 33% of those who ultimately choose nursing do so at an early age, and their choice is often based on stereotyping instead of awareness of the opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the workforce shortage due to increasing health needs of the ageing population and the attrition due to retirement of the current workforce, there is increased career opportunity for school leavers who may have traditionally chosen nursing as a career (Miller and Cummings 2009). Programmes to attract school students to nursing careers have been undertaken globally (Campbell-Heider, Sackett, and Whistler 2008;King, Hardie, and Conway 2007;Matutina 2008;Neilsen and McNally 2010). These initiatives have not been driven solely by industry workforce need.…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, the majority of the counsellors viewed nurses mainly as direct caregivers, and were unaware of other possibilities for nursing roles. Matutina (2008) notes that the severe shortage of nurses led nurse recruiters to turn to middle school students in order to influence them in choosing nursing as a career. However, a recent review indicated that research on career preferences in young people suffers from methodological problems (Matutina et al 2010).…”
Section: Choosing Nursing As a Professionmentioning
confidence: 99%